Leasing or borrowing and buying decision: a case study of Bright Soap. Issue 2 (15th April 2015) - Akhtar, Muhammad; Zada, Najeeb; Ahmad, Irfan; Zaman, Nazim
Abstract : Subject area: – Accounting, Finance, Human Resource Management and Marketing. Study level/applicability: – BBA, MBA, MS, PHD. Case overview: – Leasing or borrowing and buy decisions are very crucial in the industrial era. Every company does not possess sufficient resources to meet their investing needs. The leasing options have provided a decent way to congregate fixed assets requirements in manufacturing industry. This case mainly focuses on the dynamics of business survival. Expected learning outcomes: – To be able to evaluate the different financial and marketing options available with the company. Understand the relevance of the theory of diversification as applied to financial and production aspects; be able to evaluate the leasing, borrowing and buying options that are available in financing of fixed assets; understand the disclosure requirements in the financial statements according to International Accounting Standards (17); be able to evaluate marketing strategies including pricing options, product diversification, reaction to competition and innovation; and consider human resource policy decisions at times of change including cost-cutting measures. Supplementary materials: – Teaching Notes are available for educators only. Please contact your library to gain login details or emailsupport@emeraldinsight.com to request teaching notes.